Gender and cultural differences on death penalty support and views among Indian and U.S. college students. Issue 4 (2nd October 2018) - Lambert, Eric G.; Baker, David N.; Elechi, O. Oko; Jiang, Shanhe; Khondaker, Mahfuzul I.; Pasupuleti, Sudershan; Hogan, Nancy L.
ABSTRACT: The death penalty is used as a criminal sanction in 58 out of 193 United Nations countries across the globe, yet the vast majority of research on capital punishment views has been conducted on Western nations, particularly the United States. This study examined the level of death penalty support among college students from both India and the United States. U.S. students expressed greater support for capital punishment compared to their Indian counterparts. In addition, men in both countries were more likely to support the death penalty. The reasons for supporting or opposing capital punishment also varied by gender and nation. Men expressed greater support for reasons of retribution, deterrence, and incapacitation, whereas women were more likely to oppose capital punishment for the reasons of rehabilitation, innocence, and morality. There were differences by nation on rationales to support or oppose capital punishment. Except for incapacitation, Indian students were more polarized in their reasons to support or oppose the death penalty. The findings support the contention that gender and culture play a role in the capital punishment views of the respondents in this study.